ChemInform Abstract: Metal Chalcogenide Quantum Dots: Biotechnological Synthesis and Applications. Issue 25 (June 2016) - Mal, J.; Nancharaiah, Y. V.; van Hullebusch, E. D.; Lens, P. N. L.
Abstract: Review: 201 refs.